Physical Aspects of Heat Transfer in Ternary Hybrid Nanofluid Flow Subject to Induced Magnetic Field and Cattaneo–Christov Heat Flux - Batool, Kiran; Khouqeer, Ghada A.; Zainab, Saima; AbdelAll, Naglaa; Haq, Fazal; Sallah, Mohammed (International journal of energy research, 2025)
Ternary hybrid nanofluids (THNFs) offer superior heat transfer due to their multifunctional properties and adaptability compared to dihybrid nanofluids. Their ability to improve thermal performance, combined with their versatility in terms of chemical and physical properties, makes them an important innovation in fields such as renewable energy, electronics, automotive cooling, and industrial heat exchangers. Due to improved thermal performance and diverse usages of the THNFs, the goal of this paper is to examine the dynamics of THNF flow by a curved surface. The Cattaneo–Christov heat flux model is implemented instead of the classical Fourier principle for heat conduction. The nanoparticles of magnesium oxide (MgO) and copper (Cu), together with multiwalled carbon nanotubes (MWCNTs), are utilized for the formation of THNF. The effects of the induced magnetic field are further conceded. Flow‐governing coupled nonlinear partial differential equations (PDEs) are acquired with the implementation of boundary layer restrictions. Suitable similarity alterations are adopted to transform the PDEs into ordinary differential equations (ODEs). The transformed system is solved numerically by implementing the NDSolve built‐in function of the Mathematica package. Velocity, temperature, and the induced magnetic field have been graphically investigated under the influence of multiple aspects. The variation in skin friction force and Nusselt quantity is examined numerically. Results show that magnetic and curvature variables diminish the induced magnetic field; however, it escalates when the material variable is elevated. The suction variable decays the magnitude of heat transfer, but an opposite impact of curvature and reciprocal parameters is noticed.